Evoregions: Mapping shifts in phylogenetic turnover across biogeographic regions. Issue 12 (9th October 2020) - Maestri, Renan; Duarte, Leandro
Abstract: Biogeographic regionalization offers context to the geographical evolution of clades. The positions of bioregions inform both the spatial location of clusters in species distribution and where their most important boundaries are. Nevertheless, defining bioregions based on species distribution alone only incidentally recovers regions that are important during the evolution of the focal group. The extent to which bioregions correspond to centres of independent diversification depends on how clusters of species composition naturally reflect the radiation of single clades, which is not the case when mixed colonization occurred. Here, we show that using phylogenetic turnover based on fuzzy sets, instead of species composition, led to adequate detection of evolutionarily important bioregions, that is, regions that account for the independent diversification of lineages. Mapping those evoregions in the phylogenetic tree quickly reveals the timing and location of major shifts of biogeographic regions. Moreover, evolutionary transition zones are easily mapped, and permit the recognition of regions with high phylogenetic overlap. Our results using the global radiation of rats and mice (Muroidea) recovered four evoregions—three major evolutionary arenas corresponding to the Neotropics, a Nearctic‐Siberian, and a Paleotropical‐Australian evoregion and a fourth and fuzzy Afro‐Palearctic evoregion. Transition zones among evoregions were minimized when compared to other methods considering or not phylogenetic information, that is, the affiliation of cells to their assigned region was higher using evoregions than other approaches. Such higher affiliation values result from the lower phylogenetic overlap within evoregions, as expected when single radiations are accounted for as best as possible. Evoregions is a useful framework whenever the question is related to the identification of the most important centres of a group's diversification history and its evolutionary transitions zones.